On the foreign to native wage differential in Germany: Does the home country matter? - Stephan Brunow; Oskar Jost (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
The German labour force is expected to shrink in the next two decades due to a decline in population. Therefore, the immigration of workers from abroad could compensate potential negative effects of such decline. Is Germany competitive for immigration - i. e., do German employers pay enough to make it attractive as a destination country? We explore the wage gap between foreigners and German employees in particular and focus on different countries of origin to better understand issues related to wage setting among these groups. For this purpose, a threefold Oaxaca-Blinder decomposition is performed using a comprehensive data with a vast amount of information on a large number of workers and firms. The results suggest that most of the wage gap can be explained by observed characteristics, and in most cases, very little difference remains unexplained. We provide evidence on differences specific to the country of origin which could be taken in into consideration to attract people from abroad to better integrate them into the German labour market. – – Es ist zu erwarten, dass die Anzahl der Erwerbstätigen in Deutschland in den nächsten beiden Dekaden erheblich schrumpfen wird. Migrationsströme aus dem Ausland können die damit verbundenen negativen Effekte kompensieren. Damit geht die Frage einher, ob Deutschland für Migranten ein attraktives Ziel darstellt - zahlen Arbeitgeber genug, um für Migranten attraktiv genug zu sein? Wir analysieren das Lohngefälle zwischen ausländischen und deutschen Beschäftigten in Vollzeit und berücksichtigten dabei das Herkunftsland, um etwaige landesspezifische Unterschiede in der Lohnsetzung und Lohnstrukturen besser zu verstehen. Hierfür nutzen wir eine dreiteilige Oaxaca-Blinder Zerlegung und einen umfangreichen Datensatz mit diversen Informationen zu Individuen und Firmen. Die Ergebnisse zeigen, dass der Großteil der Lohnlücke auf Unterschiede in den beobachtbaren Charakteristiken zurückgeführt werden kann und zumeist nur sehr wenig unerklärt bleibt. Weiterhin zeigen wir Unterschiede zwischen den Herkunftsländern, die bei der Anwerbung der Beschäftigten berücksichtigt werden sollten, um die Personen besser in den Arbeitsmarkt zu integrieren.
Keywords: J31; J60; R23; 330; Migrant pay gap; country specific wage gap; inequality; Oaxaca-Blinder decomposition